Integration of remote sensing and geographical information system (GIS) for prediction of natural hazards in Hoa Binh province - Thạch, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2018)
Locating in North West direction of the Hanoi capital, Hoa Binh is a mountainous province with multitypes of landform and climate condition Thehydroelectric power station (n Hoa Binh was built on the Da river, supplying annually about 9 billion kW/hour of electric power, but it also causes a lotof effects to lower parts of the dam such as flooding, river bank erosion, etc...